OPTIMIZATION OF BIODIESEL PRODUCTION FROM CANDLENUT WASTE OIL VIA TWO-STEP ESTERIFICATION AND TRANSESTERIFICATION - Iswono, Veronica Putri; Shalomita, Natasya Geulla; Sya'ni, Mardhiyah Aliatus; Yonanda, Adam; Ruchdragani, Fajril Istiqfar; Dewi, Rini Kartika; Handaratri, Anitarakhmi (jurnal ATMOSPHERE, 2026)
The utilization of non-edible feedstocks is an important strategy in developing sustainable biodiesel, one of which is candlenut (kemiri) waste oil. This oil contains a high free fatty acid (FFA) level (10.05%), requiring a two-step process to prevent saponification during base-catalyzed transesterification. This study aims to develop biodiesel production through esterification using H₂SO₄ followed by transesterification using KOH. The esterification step reduces FFA via reaction with methanol, while transesterification converts triglycerides into methyl esters. The results show that FFA was successfully reduced to 0.435–0.708%. The highest ester content reached 98.98% (w/w), while total glycerol content was very low (0.0017–0.0019% w/w), indicating high conversion efficiency and product purity. Therefore, the applied two-step process effectively produces high-quality biodiesel from candlenut waste oil and demonstrates strong potential as a sustainable renewable energy source.